2020
DOI: 10.1002/ijop.12662
|View full text |Cite
|
Sign up to set email alerts
|

Refugee students' perspectives on inclusive and exclusive school experiences in Austria

Abstract: This paper examines refugee students' experiences in the Austrian mainstream school system. It highlights four areas: school connectedness, social exclusion, support systems and friendships. In the study, 55 refugee students between 8 and 21 years old enrolled in primary and secondary education participated in a semi‐structured interview. Data were analysed with directed qualitative content analysis, whereby codes were created deductively and inductively. Students stressed the importance of schooling in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…Understanding the relationship between PB exposure and PTSS is important for widening our comprehension of the significant sequelae experienced by the refugee schoolchildren. The screened participants reported bullying as a problem and verified the findings of other studies (Bešić et al, 2020; Bjereld et al, 2015; Mynard et al, 2000), which reported that approximately 50–60% refugee students suffered from PB at least once a month. The results of this study supported the fact that victims of bullying may experience PTSS in different settings and situations, including workplaces, schools, and public places (Balducci et al, 2011; Crosby et al, 2010).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Understanding the relationship between PB exposure and PTSS is important for widening our comprehension of the significant sequelae experienced by the refugee schoolchildren. The screened participants reported bullying as a problem and verified the findings of other studies (Bešić et al, 2020; Bjereld et al, 2015; Mynard et al, 2000), which reported that approximately 50–60% refugee students suffered from PB at least once a month. The results of this study supported the fact that victims of bullying may experience PTSS in different settings and situations, including workplaces, schools, and public places (Balducci et al, 2011; Crosby et al, 2010).…”
Section: Discussionsupporting
confidence: 85%
“…Culturally, certain aggressive behavior toward refugees may not be considered abuse or bullying, which is an excuse for the school administration to disregard this behavior (Bešić et al, 2020). This could increase the possibility of PB in refugee students at school and its consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…School belonging is defined by the extent to which a student feels supported, accepted, connected, engaged and included, where a higher sense of belonging correlates to better academic outcomes (Allen et al., 2018; Pittman & Richmond, 2007). Although this study focused on Syrian adolescents in U.S. schools, increasing sense of school belonging in other resettlement countries has been found to be as equally important (Bešić et al., 2020). Parents in this study communicated a sense of belonging and satisfaction when teachers expressed kindness and care to their children as well as encouraged families to stay in the district.…”
Section: Implications For School Psychologistsmentioning
confidence: 99%
“…However, educational systems in the Global North, where political and social circumstances are far more stable and secure, such as in Austria, are shaped by exclusion processes as well, albeit in a more subtle way (Husny & Fasching, 2022;Jørgensen et al, 2021). This particularly applies to young refugees who are often confronted with uncertain residence status, discriminatory perceptions, and a lack of viable labor market perspectives (Bešić et al, 2020;Eggenhofer-Rehart et al, 2018). Therefore, in contrast to approaches that focus on "job-skill mismatches" (Bandara, 2019) and thus suggest a deficit-oriented individualistic perspective on the transition into the workforce, critical social science perspectives pay attention to political, societal, institutional, and structural levels, which (re)produce inequality (e.g., Dahmen, 2021;Waechter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%